2018
DOI: 10.1002/apj.2218
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on drag reduction by coupled addition of nonionic polymer poly(ethylene oxide) and cationic surfactant cetyltrimethyl ammonium chloride

Abstract: More and more attention is paid to the synergistic drag reduction by polymers and surfactants because there are serious disadvantages of the drag reduction by them alone. In order to understand the synergistic effect of the drag reduction by polymers and surfactants, in-depth investigations are performed on the drag reduction behavior by simultaneous addition of nonionic polymer poly(ethylene oxide) (PEO) and cationic surfactant cetyltrimethyl ammonium chloride (CTAC) in a two-dimensional channel flow. The sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Grafting a short branch on the main chain of the polymer can reduce the drag reduction performance while grafting a small number of long branches can improve the drag reduction effect 31 . The introduction of a hydrophobic polymerizable surfactant group into the main chain of a hydrophilic polymer molecule could give the polymer friction resistance, and reduce interfacial tension on the oil–water surface 11 . This approach could produce molecule properties similar to those of a surfactant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Grafting a short branch on the main chain of the polymer can reduce the drag reduction performance while grafting a small number of long branches can improve the drag reduction effect 31 . The introduction of a hydrophobic polymerizable surfactant group into the main chain of a hydrophilic polymer molecule could give the polymer friction resistance, and reduce interfacial tension on the oil–water surface 11 . This approach could produce molecule properties similar to those of a surfactant.…”
Section: Resultsmentioning
confidence: 99%
“…31 The introduction of a hydrophobic polymerizable surfactant group into the main chain of a hydrophilic polymer molecule could give the polymer friction resistance, and reduce interfacial tension on the oil-water surface. 11 This approach could produce molecule properties similar to those of a surfactant. On the other hand, the hydrophobic surfactant groups, driven by "entropy" in water, could gradually associate to form a supramolecular network structure under the influence of intermolecular interactions such as hydrogen bonds, ion bonds and van der Waals forces, including the hydrogen bond supramolecular aggregation state, 14 (Figure 2).…”
Section: Synthesis Processmentioning
confidence: 99%
See 2 more Smart Citations
“…The commonly used drag reduction agents can be divided into polymer and surfactant, each of which has its own advantages and disadvantages (see Table 2). 9,10 Because surfactant can overcome the shortcomings of polymer and have reversibility of degradation, it is favored in the field of turbulent drag reduction. Many scholars have carried out amounts of research on the drag reduction characteristics and drag reduction mechanism of surfactant and found that the drag reduction mechanism of surfactant is closely related to its rheological characteristics 11 .…”
Section: Introductionmentioning
confidence: 99%